Previdência social e desigualdade regional no Brasil: Uma abordagem multiescalar - Marcelo Abi-Ramia Caetano; Leonardo Monteiro Monasterio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The aim of the paper is to analyze the impact of the General Social Security System (RGPS) on regional disparities in Brazil. The study examines the impact of social security on regional income distribution at different scales by means of econometric tests, and conventional measures of inequality, such as the Gini and progressiveness indexes. The econometric results, with appropriate controls, suggest that social security transfers are inversely correlated with gross domestic product (GDP) per capita. This indicates some regional progressivity of social security transfers in Brazil. At the municipal level, a 1% increase in GDP per capita is associated with a 0.73% increase in the revenues and benefits ratio of 0.73%. Similarly, the analysis of the regional Gini index for the distribution of GDP per capita by municipality shows that such transfers reduce that inequality measure of 0.39 to 0.35. The study concludes that RGPS taxes richer regions to finance benefits in impoverished areas at municipal, micro or mesoregional levels. At all scales, RGPS shows its progressivity.
Keywords: H55; R12; H5; 330; social security; progressivity; regional inequality